Pengembangan Pengelolaan Perangkat Pembelajaran Praktik Berbasis Lingkungan dalam Penunjang Pembelajaran Kimia - Eristiana, Eristiana; Warlizasusi, Jumira; Sutarto, Sutarto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to develop practical learning tools based on the environment to support chemistry learning for students at MAN 2 Lahat. This research uses a 3-D model; define (defining) by analyzing the students, teachers and materials. Design (Planning) by making product designs and developing (development), namely conducting validation and particularity tests. Implementation of practicum at MAN 2 Lahat in class X MIA, X IIS and X IIK students used an environment-based practicum method with enthusiasm, enthusiasm and a sense of responsibility. The validation results of the experts reached a score of 3.87 which was categorized as very valid and the test of environment-based learning tools reached a very practical implementation percentage of 96.67%. In conclusion, the environment-based practical learning tools developed to support chemistry learning for students at MAN 2 Lahat are declared valid and feasible to be used to support learning. Keywords: Development, Management, Practical Learning Devices